Types of Statements on Emotion in Music - Krämer, Benjamin (The Nordic Journal of Aesthetics, 2012)
The question of emotion in music is addressed from a linguistic perspective, providing a typology of statements that can be made about that topic. In particular, it is analyzed how an interlocutor could react to such statements uttered by another person, and whether or how the content of the statements could be refuted by the listener, and possibly corroborated by the speaker. Furthermore, it is briefly discussed which theories of emotion in music are compatible with the respective types of statement and what illocutionary and perlocutionary function they may serve.